Potassium Solubilizing Microorganisms for Sustainable Agriculture 2016
DOI: 10.1007/978-81-322-2776-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Plant Physiology and Antioxidant Enzymes for Alleviating Salinity Stress by Potassium-Mobilizing Bacteria

Abstract: Potassium (K) is among the most important essential macronutrients for plant growth. About 98 % of the potassium in the earth's crust exists in insoluble forms as rocks and silicate minerals, resulting in very low concentrations of soluble potassium in the soil for plant growth and development. Rhizosphere bacteria are a group of metal-mobilizing, plant growth-promoting bacteria having the ability to solubilize potassium from insoluble potassium rocks. KSM (a potassium-solubilizing microorganism) is a metal-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Plant height and dry weight of seedlings are common characteristics to determine plant growth status. Previous studies proposed the use of plant height and dry weight as screening tests for salt tolerance under salt stress [ 30 , 31 ]. In this study, we found that B2 significantly increased plant height and dry weight of maize ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant height and dry weight of seedlings are common characteristics to determine plant growth status. Previous studies proposed the use of plant height and dry weight as screening tests for salt tolerance under salt stress [ 30 , 31 ]. In this study, we found that B2 significantly increased plant height and dry weight of maize ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, Piriformospora indica colonization into Brassica campestris subspecies chinensis confered salinity tolerance and higher expression levels of some specific salt tolerance genes, including SOS1 and SOS2, NHX-type [ 116 ]. The effective colonization of Piriformospora indica also elevated the antioxidant enzymes SOD; POD, CAT and elevated phytohormones, mainly SA, GA, that are directly involved in stress tolerance [ 117 ].…”
Section: Endophyte-mediated Oxidative Stress Managementmentioning
confidence: 99%
“…Several studies have successfully selected salt-tolerant PGPB displaying diverse plant benefits under saline stress, including efficient halotolerant PSB and KSB (Jha et al, 2011;Rojas-Tapias et al, 2012;Zhao et al, 2016;He et al, 2018;Ashfaq et al, 2020;Rojas-Solis et al, 2020). Jha and Subramanian (2016) reported KSB belonging to different genera that not only mobilized K from insoluble forms under salinity levels but also protect plants from salinity injury by enhancing their growth-related physiology. Such microorganisms reduced lipid peroxidation and increased plant cell stability under salt stress.…”
Section: Concomitant Use Of Rocks and Weathering Bacteria As Fertilizmentioning
confidence: 99%